Food consumption of saltwater crocodile (Crocodylus Porosus) in a reptile farm of Bangladesh - Hossain, Md Sakhawat; Jaman, M Firoj; Ahmed, Mushtaq; Rahman, Md Mokhlesur; Uddin, Mayen (Bangladesh Journal of Zoology, 2015)
An extensive study was conducted on food consumption and feeding behavior of saltwater crocodile (Crocodylus porosus) in the Reptiles Farm Ltd. (RFL) located at Hatiber village, Bhaluka, Mymensingh. The study was mainly based on direct observation and previous data collected by the technicians of the RFL. Average temperature (0C) in the farm area was significantly correlated with average food consumption (g) of the hatchlings (r = 0.714, p<0.05, n = 12). The average temperature and the average food consumption were highest in August and it was 30.5 ±5.5 0C and 45.02 ±13.05 g, respectively. Monthly feeding of hatchlings was different in three individual tubs. The highest food consumption was in August although; hatcherys temperature was constant (320C). Crocodilians can increase their level of consumption during warmer months of the year while decreasing it in the cooler months. The highest quantity of food was given in October, probably for accumulation of fat in their body which would provide energy in the whole winter season. A total of 93.1 kg provisioned food was supplied to an adult crocodiles per year. Food consumption of crocodile is temperature dependent and the potentiality of crocodile farming is embedded in it, by considering this factor it may gain prosperity of crocodile farming in our country. Bangladesh J. Zool. 41(2): 173-179, 2013